PERENCANAAN PERSEDIAAN BAHAN BAKU JUMBO DRAGON ROLL DENGAN METODE MATERIAL REQUIREMENT PLANNING (MRP) DI RESTORAN SUSHI TEI - Mariaty, Linda; Mutiara, Piala (Jurnal Sains dan Teknologi ISTP, 2023)
To meet consumer demand which often sells out and to maintain public trust in Sushi Tei, Sushi Tei needs to maintain the quality of its food, and the food must always be fresh. Therefore, the author conducted research on supplies at the Sushi Tei restaurant and saw a problem that the food ordered was sometimes sold out. So in this final assignment the researcher conducted research to solve the problems that occurred at the Sushi Tei restaurant. To solve this problem, researchers used the MRP (Master Requirement Planning) method. The results obtained from the research include, the average forecast demand for the Jumbo Dragon Roll menu at the Tei Teuku Daud Sushi Restaurant in the period May 2023 to April 2024 is 342 portions / month. The amount of raw material supplies per month that must be provided to meet demand for Jumbo Dragon Roll during the period May 2023 to April 2024 is: inari rice 17,067 grams/month, seaweed 342 pieces/month, tempura shrimp 683/month, eel 10,240 grams /month, crabstick 1,767 sticks/month, Japanese cucumber 86 sticks/month, avocado 86 pieces/month, fish eggs 6,827 grams/month, mayonnaise sauce 17,067 grams/month.